Art Innovation Learning Guidance For Kindergarten Teacher - Kustiawan, Usep; Wulandari, Retno Tri; Tirtaningsih, Munaisra Tri; Astuti, Wuri (International Journal of Educational Research & Social Sciences, 2023)
The purpose and scope of this guidance activity are to provide kindergarten teachers in Sukun District, Malang City, the knowledge and skills about designing and implementing early childhood integrated art innovation learning to improve the effectiveness and quality of children’s art learning process in kindergarten as part of their job. Guidance and training methods that will be used in this activity are 1) delivery of material and discussion about the development of early childhood art skills and early childhood integrated art innovation; 2) guidance and practice in groups to discuss innovation and designing one learning material package of early childhood integrated art including art, dance, music, and drama literature; 3) Demonstration and simulation to demonstrate the early childhood integrated art innovation learning activity as a part of art class in kindergarten; 4) discussion and evaluation to get feedback both about the process and results of guidance and practice activities. The results obtained are 1) Non-Physical results; from the evaluation of the final results, it can be concluded that 90% (out of 40 participants) have understood the knowledge and skills about making early childhood integrated art innovation to improve the effectiveness and quality of children’s art learning process in kindergarten as part of their job; 2) Physical Result; obtained by the participants from the guidance and training activities are products in the form of early childhood integrated art innovation learning types about various themes and titles. In general, this guidance and training activity is considered successful because, at the end of the activity, all participants have the knowledge and skills about designing and implementing early childhood integrated art innovation learning to improve the effectiveness and quality of children’s art learning process in kindergarten as part of their job.